In vitro pharmacologic profiling aids systemic toxicity assessment of chemicals - Matthew Burbank; Predrag Kukic; Gladys Ouedraogo; J. Gerry Kenna; Nicola J. Hewitt; Duncan Armstrong; Annie Otto-Bruc; Johanna Ebmeyer; Mareike Boettcher; Ian Willox; Catherine Mahony (Toxicology and Applied Pharmacology, 2024)

Pyrrolizidine alkaloid-induced transcriptomic changes in rat lungs in a 28-day subacute feeding study - Julia Buchmueller; Heike Sprenger; Johanna Ebmeyer; Josef Daniel Rasinger; Otto Creutzenberg; Dirk Schaudien; Jan G. Hengstler; Georgia Guenther; Albert Braeuning; Stefanie Hessel-Pras (Archives of Toxicology, 2021)
Pyrrolizidine alkaloids (PAs) are secondary plant metabolites synthesized by a wide range of plants as protection against herbivores. These toxins are found worldwide and pose a threat to human health. PAs induce acute effects like hepatic sinusoidal obstruction syndrome and pulmonary arterial hypertension. Moreover, chronic exposure to low doses can induce cancer and liver cirrhosis in laboratory animals. The mechanisms causing hepatotoxicity have been investigated previously. However, toxic effects in the lung are less well understood, and especially data on the correlation effects with individual chemical structures of different PAs are lacking. The present study focuses on the identification of gene expression changes in vivo in rat lungs after exposure to six structurally different PAs (echimidine, heliotrine, lasiocarpine, senecionine, senkirkine, and platyphylline). Rats were treated by gavage with daily doses of 3.3 mg PA/kg bodyweight for 28 days and transcriptional changes in the lung and kidney were investigated by whole-genome microarray analysis. The results were compared with recently published data on gene regulation in the liver. Using bioinformatics data mining, we identified inflammatory responses as a predominant feature in rat lungs. By comparison, in liver, early molecular consequences to PAs were characterized by alterations in cell-cycle regulation and DNA damage response. Our results provide, for the first time, information about early molecular effects in lung tissue after subacute exposure to PAs, and demonstrates tissue-specificity of PA-induced molecular effects.

Hepatotoxic pyrrolizidine alkaloids induce DNA damage response in rat liver in a 28-day feeding study - Johanna Ebmeyer; Josef Daniel Rasinger; Jan G. Hengstler; Dirk Schaudien; Otto Creutzenberg; Alfonso Lampen; Albert Braeuning; Stefanie Hessel-Pras (Archives of Toxicology, 2020)
Pyrrolizidine alkaloids (PA) are secondary plant metabolites that occur as food and feed contaminants. Acute and subacute PA poisoning can lead to severe liver damage in humans and animals, comprising liver pain, hepatomegaly and the development of ascites due to occlusion of the hepatic sinusoids (veno-occlusive disease). Chronic exposure to low levels of PA can induce liver cirrhosis and liver cancer. However, it is not well understood which transcriptional changes are induced by PA and whether all hepatotoxic PA, regardless of their structure, induce similar responses. Therefore, a 28-day subacute rat feeding study was performed with six structurally different PA heliotrine, echimidine, lasiocarpine, senecionine, senkirkine, and platyphylline, administered at not acutely toxic doses from 0.1 to 3.3 mg/kg body weight. This dose range is relevant for humans, since consumption of contaminated tea may result in doses of ~ 8 µg/kg in adults and cases of PA ingestion by contaminated food was reported for infants with doses up to 3 mg/kg body weight. ALT and AST were not increased in all treatment groups. Whole-genome microarray analyses revealed pronounced effects on gene expression in the high-dose treatment groups resulting in a set of 36 commonly regulated genes. However, platyphylline, the only 1,2-saturated and, therefore, presumably non-hepatotoxic PA, did not induce significant expression changes. Biological functions identified to be affected by high-dose treatments (3.3 mg/kg body weight) comprise cell-cycle regulation associated with DNA damage response. These functions were found to be affected by all analyzed 1,2-unsaturated PA. In conclusion, 1,2-unsaturated hepatotoxic PA induced cell cycle regulation processes associated with DNA damage response. Similar effects were observed for all hepatotoxic PA. Effects were observed in a dose range inducing no histopathological alterations and no increase in liver enzymes. Therefore, transcriptomics studies identified changes in expression of genes known to be involved in response to genotoxic compounds at PA doses relevant to humans under worst case exposure scenarios.

The pyrrolizidine alkaloid senecionine induces CYP-dependent destruction of sinusoidal endothelial cells and cholestasis in mice - Stefanie Hessel-Pras; Albert Braeuning; Georgia Guenther; Alshaimaa Adawy; Anne-Margarethe Enge; Johanna Ebmeyer; Colin J. Henderson; Jan G. Hengstler; Alfonso Lampen; Raymond Reif (Archives of Toxicology, 2020)